Analisis Model Pembelajaran STEAM sebagai Strategi Pengembangan Numerasi Aljabar di Sekolah Menengah Pertama - Suharni, Suharni; Sulistiawati, Ida; Irawan, Nico (STKIP Taman Siswa Bima, 2024)
This study aims to analyze the effectiveness of implementing the STEAM (Science, Technology, Engineering, Arts, and Mathematics) Learning Model as a strategy to develop algebraic numeracy in junior high schools (SMP). The research employed a quasi-experimental design, specifically the pretest-posttest non-equivalent control group design, involving 120 seventh-grade students divided into an experimental group (STEAM-based learning) and a control group (conventional learning). The main instruments included an algebraic numeracy test, a learning motivation questionnaire, observation sheets, and interview guidelines to explore qualitative aspects. Quantitative data analysis was performed using t-tests and effect size calculations to measure differences in learning outcome improvement between the two groups. The results showed that the experimental group achieved a significantly higher increase in algebraic numeracy scores compared to the control group. Moreover, classroom observations and interviews with teachers and students revealed that STEAM-based instruction enhances active participation, learning motivation, and collaborative skills. This positive impact is partly driven by the interdisciplinary integration, which makes algebraic material more contextual and engaging. Despite some obstacles, such as limited facilities and time constraints, the overall findings conclude that the STEAM Learning Model effectively contributes to strengthening students’ understanding of algebraic concepts in junior high schools. The practical implications of these findings underscore the need for teacher support and training, curriculum adjustments, and adequate resources to expand the implementation of STEAM across various schools